GE_GERICHTE P/20321/2016 vom 27. Februar 2018 - GE Cour de justice (2018)
LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE ; DÉPASSEMENT(CIRCULATION) ; DISTANCE ENTRE VÉHICULES | LCR.90; LCR.34.al4; LCR.35.al1